Solar Drying of Onion Scapes: A Sustainable Solution for Agriculture and Industry - Laouini, Abdeldjalil; Zine Ali; Guediri Samir (Sousse - Tunisia, 2024)
This study investigates the use of solar drying for processing onion scapes, a key agricultural product in southern Algeria. The scapes were harvested early, dried, and repurposed for medicinal applications and livestock feed, providing an environmentally friendly and economically viable solution. The experiment was conducted at the Renewable Energy Development Research Unit in Arid Zones (UDERZA) at the University of El Oued, where an indirect solar dryer was used, and solar radiation and temperature data were recorded. Results showed that the MidilliKucuk model was the best fit for predicting drying kinetics, with an R2 value of 0.99978, a chi-square value of 4.3×10^(-5), and an RMSE of 0.00651. The effective moisture diffusivity was calculated at 6.83598E-06 m²/s, confirming that solar drying is a viable and sustainable solution for processing onion scapes. الملخص (باللغة العربية) تتناول هذه الدراسة استخدام التجفيف الشمسي في معالجة سيقان البصل، وهو منتج زراعي رئيسي في جنوب الجزائر. تم حصاد السيقان مبكرًا، وتجفيفها، وإعادة استخدامها في التطبيقات الطبية وتغذية الماشية، مما يتيح حلاً صديقًا للبيئة وذا جدوى اقتصادية. أُجريَت التجربة في وحدة البحث لتطوير الطاقات المتجددة في المناطق الجافة (UDERZA) بجامعة الوادي، حيث استخدم مجفف شمسي غير مباشر، وسُجّلت بيانات الإشعاع الشمسي ودرجات الحرارة. أظهرت النتائج أن نموذج "مديلي كوتشوك" هو الأنسب للتنبؤ بحركيات التجفيف،
Intervention
Keywords: Solar Drying; Onion; Scapes; Diffusivity; Drying Kinetics; المجففات الشمسية; قصبات البصل; حركية التجفيف; البصل